1965
DOI: 10.1136/bmj.1.5428.158
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Ankle-jerk in the Diagnosis and Management of Thyroid Disease

Abstract: SummaryThe chromosomes were examined in preparations made directly (without culture) from biopsy material from the affected area in eight cases with presumptive precancerous change (carcinoma-in-situ or dysplasia) of the cervix uteri and one of the vagina. The eight cervical lesions were entirely intraepithelial, but the vaginal one was associated with a small invasive carcinoma.-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In our preliminary study' of the 30 euthermic patients, we confirmed the findings of many previous workers that hypothyroidism prolongs both the contraction and the relaxation phases of the Achilles tendon reflex (Ord, 1884; Lambert et al., 1951; Fogel et al, 1962;Sherman et al, 1963;Miles and Surveyor, 1965;Abraham et a!., 1966;Nuki and Bayliss, 1968). The relaxation phase was prolonged more than the contraction phase, the mean (± 1 S.D.)…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In our preliminary study' of the 30 euthermic patients, we confirmed the findings of many previous workers that hypothyroidism prolongs both the contraction and the relaxation phases of the Achilles tendon reflex (Ord, 1884; Lambert et al., 1951; Fogel et al, 1962;Sherman et al, 1963;Miles and Surveyor, 1965;Abraham et a!., 1966;Nuki and Bayliss, 1968). The relaxation phase was prolonged more than the contraction phase, the mean (± 1 S.D.)…”
Section: Resultssupporting
confidence: 90%
“…Slow ankle jerks are characteristic of myxoedema (Ord, 1884) and they have often been studied (Fogel et al, 1962;Sherman et al, 1963;Miles and Surveyor, 1965;Abraham et al, 1966;Nuki and Bayliss, 1968). Indeed, delayed relaxation of the ankle jerk has routinely been used in the Mayo Clinic for about 50 years as an aid in the diagnosis of myxoedema (Lambert et al, 1951).…”
Section: Discussionmentioning
confidence: 99%
“…The photomotogram (or some other measure of the ankle-jerk), although less reliable than most other tests and hence less suitable as a screening procedure, is not to be abandoned, because it is easy to perform, it measures a different parameter than other tests, i.e. the response of peripheral tissues to thyroid hormones and thus the metabolic status of the patient (16), and so it is suitable for the assessment of patients under treatment (24,25,37). Under these circumstances, the main thyroid hormone may be triiodothyronine and so the value of the serum PB I or thyroxine determinations is severely limited (8), whereas in vivo uptake measurements can not be used at all, except for very early uptake measurements, for which there is no evidence that they correlate closely with the metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include testing capillary blood glucose concentration during insulin treatment and testing blood clotting times during warfarin therapy. An early example of systematic monitoring to ensure that treatment was within a therapeutic range was the measurement of ankle reflex time as a surrogate for thyroid status [5].…”
Section: Monitoring In Therapeuticsmentioning
confidence: 99%